2018
DOI: 10.3389/fnhum.2018.00117
|View full text |Cite
|
Sign up to set email alerts
|

Brain Atrophy and Reorganization of Structural Network in Parkinson's Disease With Hemiparkinsonism

Abstract: Hemiparkinsonism duration in patients with Parkinson's disease (PD) is a key time window to study early pathology of PD. We aimed to comprehensively explore the alterations of deformation and structural network in PD patients with hemiparkinsonism, which could potentially disclose the early biomarker for PD. Thirty-one PD patients with hemiparkinsonism and 37 age- and gender- matched normal controls were included in the present study. First of all, we normalized the left hemisphere of structural images as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
2
22
0
1
Order By: Relevance
“…Nodal properties could be divided to two field, nodal centralities (e.g., nodal degree and nodal betweenness) and nodal cliquishness properties (e.g., nodal local efficiency and nodal clustering coefficient) ( 35 , 36 , 57 ). In our study, we showed a shift between nodal centralities and nodal cliquishness properties in PD-pRBD.…”
Section: Discussionmentioning
confidence: 99%
“…Nodal properties could be divided to two field, nodal centralities (e.g., nodal degree and nodal betweenness) and nodal cliquishness properties (e.g., nodal local efficiency and nodal clustering coefficient) ( 35 , 36 , 57 ). In our study, we showed a shift between nodal centralities and nodal cliquishness properties in PD-pRBD.…”
Section: Discussionmentioning
confidence: 99%
“…The only differences between Weak-Visuospatial class and the Typical class were weakness in visuospatial functioning, and atrophy in left rolandic operculum including the precentral gyrus and the insula. In PD, atrophy of the Rolandic operculum has been seen in patients with mild to moderate diseases [33]. In particular, left insular atrophy has been shown to correlate with visuospatial performance in PD-MCI [34].…”
Section: Discussionmentioning
confidence: 99%
“…As numerously documented, along the disease trajectory, most PD patients would experience a special stage (Hoehn-Yahr stage = 1 and 1.5), hemiparkinsonism [ 6 , 21 , 46 ], when motor symptoms only occur in the unilateral side of limbs while the other side of limbs is possibly unaffected. In this section, we aimed to extend previous findings to the patients in this special stage.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the sample sizes included in these studies were relatively small. Last but not least, none of them tested the hypothesis in both PD patients with bilaterally asymmetrically affected limbs, and with unilaterally affected limbs (known as hemiparkinsonism [ 6 , 21 ]).…”
Section: Introductionmentioning
confidence: 99%